2022
DOI: 10.53299/diksi.v3i2.214
|View full text |Cite
|
Sign up to set email alerts
|

Improving Students Reading Fluency through Audiobooks in Remote Learning

Abstract: Due to the Covid-19 pandemic, the teaching and learning process has become more challenging and stressful. Students are expected to do self-learning without being directly guided when attending the class is not possible, while the teachers must keep encouraging the students to learn independently. At the same time, the teachers also have to think about alternative methods and materials for remote learning. Especially for those teachers who teach EFL students, they have to figure out certain materials that meet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…A study by (Meiristiani et al, 2022) found that the transformation of literary works and texts from the community were transformed from text to audio formats, such as audiobooks and podcasts, to develop digital literacy media for language and literature education for the community. (Pratiwi et al, 2022) said that the implications of audiobooks affect students' ability to become more fluent in reading. The application of Storynory audiobooks in teaching reading narrative texts shows a good response from students and teachers where they enjoy and easily understand the text, can help students in pronunciation of words, and can introduce and increase students' vocabulary or foreign words in the text (Tsany, 2021).…”
Section: Trends In the Development Of Audiobooks Past And Presentmentioning
confidence: 99%
“…A study by (Meiristiani et al, 2022) found that the transformation of literary works and texts from the community were transformed from text to audio formats, such as audiobooks and podcasts, to develop digital literacy media for language and literature education for the community. (Pratiwi et al, 2022) said that the implications of audiobooks affect students' ability to become more fluent in reading. The application of Storynory audiobooks in teaching reading narrative texts shows a good response from students and teachers where they enjoy and easily understand the text, can help students in pronunciation of words, and can introduce and increase students' vocabulary or foreign words in the text (Tsany, 2021).…”
Section: Trends In the Development Of Audiobooks Past And Presentmentioning
confidence: 99%